THE EFFECT OF TOTAL COMMUNICATION APPROACH TOWARDS THE TEXT RETELLING ABILITY OF HEARING IMPAIRMENT STUDENTS - Khusnul Khotimah; Wiwik Dwi Hastuti (Department of Special Education, 2016)
The purpose of this research was to know the effect of the total communication approach towards the hearing impairment students’ text retelling ability in the third grade of SDLB Kepanjen Malang. This research was experimental study using A-B-A Single Subject Research (SSR) design. The result of the study showed that the total communication approach affected the student’ text retelling ability. The analysis showed that the intervention gave an effect to the improvement of the target’s behaviour.Penelitian ini bertujuan untuk mengidentifikasi pengaruh pendekatan komunikasi total terhadap kemampuan menceritakan kembali isi bacaan siswa tunarungu kelas 3 di SDLB Kepanjen Malang. Pendekatan yang digunakan dalam penelitian ini yaitu bersifat eksperimen dengan metode SSR (Single Subject Research) desain A-B-A. Hasil penelitian ini menunjukkan bahwa pendekatan komunikasi total yang dijadikan sebagai intervensi kepada siswa tunarungu ternyata memiliki pengaruh terhadap peningkatan kemampuan dalam menceritakan kembali isi bacaan siswa tunarungu.